Women Living With Breast and Cervical Cancer in the Community: The Face of Surabaya Nowadays - Sari, Ni Putu Wulan Purnama (Indonesian Journal of Cancer, 2018)
Background: Cervical cancer and breast cancer are the two top leading cases of female cancer in Indonesia. Being the 2nd largest city in Indonesia, Surabaya is being populated by more than 1.5 million females in 2017. This study aimed to describe the demographic characteristic of women living with cervical and breast cancer in order to show the current picture of female cancer situation in Surabayan communities nowadays. Substantial to it, the correlation between time of first diagnosis and type of therapy with current stage of cancer were analyzed to evaluate the cancer management effectiveness in community context.Methods: This cross-sectional study involved six (9.68%) Public Health Centers (PHCs) among 62 PHCs in Surabaya, Indonesia, which were selected by one stage cluster random sampling. There were 140 and 139 women living with cervical and breast cancer participated in this study respectively (n=279). Self-developed demographic questionnaire was used to collect the data. Descriptive statistic, Spearman Rank correlation test, and Mann-Whitney U test were used in data analysis (α<.05).Results: Overall, most respondents were married (77.06%) and were housewives (59.14%). They were high school graduated at majority (44.44%). Family support came from spouse and children (70.25%). Those with breast cancer mostly aged middle-up adulthood (56.12%), while older aged were found in respondents with cervical cancer (72.86%). The majority had been diagnosed with cancer for less than five years (81.36%), but there was a tendency that the longer life expectancy was found in those with cervical cancer. More cervical cancer respondents with advanced stage were found to be long-term survivors (25%). The first time of diagnosis and the type of therapy were significantly different between cases (p=.039 and p=.000 respectively), but the current stage of cancer was not significantly different (p=.239). There was a quite strong correlation between time of first diagnosis and current stage of cancer (ρ = -.409; p=.000), but there was no significant correlation between type of therapy and current stage of cancer (p=.147).Conclusions: The demographic characteristic of women living with cervical and breast cancer has been slowly shifting from elderly or late adulthood, to middle and early adulthood. The first time of diagnosis and the type of therapy were significantly different between cases, but the current stage of cancer was not significantly different. There was a strong significant correlation between time of first diagnosis and current stage of cancer in cervical and breast cancer.